Meta-Analysis: Determining Hedging on Foreign Exchange - Pradhani, Tri Buana Wira; Sariah, Sariah; Hwihanus, Hwihanus; Ratnawati, Tri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Hedging is an action taken by investors, both individuals and governments and companies to protect value due to the risk of price changes. Investors and companies must have good risk management. They must pay attention to, identify, mitigate, and control risks, to survive amidst risk uncertainty. Hedging aims to deal with risks caused by changes in interest rates, exchange rates, and prices of goods, especially when using foreign exchange. This research aims to discuss further the determination of hedging on foreign exchange, using the meta-analysis method. The data source used is secondary data, namely data obtained from previous research. The results show that almost all companies hedge to minimize risk, although there is a multinational company that does not do so.